Controlling Factors of Artificial Irregularities Triggered by Chemical Release at Low Latitude Ionosphere - Jing‐Fan Gao; Zheng‐Wen Xu; Li‐Xin Guo; Kun Xue; Hai‐Sheng Zhao (Space Weather)
Abstract The chemical release for trigging instabilities is a challenging topic in the ionosphere since 1970s. It is a helpful tool to both recognize the physical mechanism for modeling space weather and mitigate adverse effects on technological systems. Based on the well‐developed instability simulation, the rate of change of total electron content index (ROTI) theory is employed as a diagnosis method in this paper. It is used to study the instability inducing effects or scintillation controlling effect of chemical release for the first time. The main controlling factors of the chemical release are investigated. It is found that the release amount, release altitude and the initial growth rate of the ambient ionosphere are of great importance to the instability evolution and consequent scintillation effects. First, the plasma bubble induced by chemical release will rise and penetrate to the upper ionosphere, no matter what the ambient growth rate is. However, the ambient growth rate will determine the induced scintillation regime. Second, the release altitude will significantly affect the instability evolving time and scintillation intensity. There only exist a threshold of the release amount for moderate scintillation. Finally, the release amount could dominate the bifurcation process, in which the plasma bubble will deform and extend laterally. It provides an insight into the scintillation effect induced by chemical release by using the ROTI estimation. As a result, this work is a step further for the challenging topic of chemical release, and so as to be helpful for the follow‐up active space experiments.